Utilization of Geospatial Information in Daily Life Expression and Analysis of Dynamic Life Activity - Sekimoto, Yoshihide; Kawahara, Yasuhiro (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book focuses on geospatial information in living spaces, providing many examples of its collection and use as well as discussing the problems of how it is used and its future prospects. Geospatial information science is in the process of evolving and being systematized, with the technical and usage aspects of the real world stimulating each other. This book systematizes the technical aspects of positioning; of geography, which manages and represents what is measured in units of earth coordinates; and of data science, which aims to efficiently express and process geographic information, all by introducing contemporary examples that are systematized with regard to their use in our living spaces. Examples of geospatial information used in almost all aspects of our lives, including urban areas, transportation, disaster prevention, health and medical care, agriculture, forestry and fisheries, culture, ecology, and topography, are presented, along with examples of their use in each area. One of the major features of this book is that it describes the use of data from earthquake disasters that is unique to Japan, as well as the use of open data and personal data in Japan, which is a trend that is gaining attention in many countries. In this way the book systematically describes events and circumstances in living spaces that are revealed by the expression and analysis of geospatial data, with case studies and discusses their use in the IoT era.
Chapter 1. Fundamentals and Applications of Geospatial Information (Yasuhiro Kawahara, Yoshihide Sekimoto) -- Part I Expression of Geospatial Information -- Chapter 2. Base Map Development and Surveying in Japan (Toshikazu Seto) -- Chapter 3. Various Representations and Processing Techniques of Geospatial Information - Appropriate Control of Big Data Behind (Yoshihide Sekimoto) -- Part II Mobile Communications and Positioning -- Chapter 4. Ground-based and Space-based Positioning (Yasuhiro Kawahara) -- Chapter 5. Observation from Space - Remote sensing (Masahiko Nagai) -- Part III Utilization of Geospatial Information in Daily Life -- Chapter 6. Applications in Urban Facility and Land Management - from Urban Facility Management to Smart Cities (Yoshihide Sekimoto) -- Chapter 7. Applications in Transportation Systems and Mobile Devices - Capturing the Movement of People (Yoshihide Sekimoto) -- Chapter 8. Applications in Crime Prevention (Ikuho Yamada) -- Chapter 9. Applications in Health and Healthcare (Ikuho Yamada) -- Chapter 10. Application in Times of Disaster - Through the Great Hanshin Earthquake, the Great East Japan Earthquake, and Covid-19 (Yoshihide Sekimoto) -- Chapter 11. Utilization in Agriculture, Forestry, and Marine Management (Masahiko Nagayama, Yasuhiro Kawahara) -- Chapter 12. Utilization in Behavior, Ecology, and Cultural Property Surveys (Yasuhiro Kawahara) -- Chapter 13. International Applications (Yoshihide Sekimoto) -- Part IV Open Data and Personal Data in the Use of Geospatial Information -- Chapter 14.The advent of a participatory data society and the use of open data (Toshikazu Seto) -- Chapter 15. Future geospatial information in harmony with advanced technology and human life (Yoshihide Sekimoto, Yasuhiro Kawahara).
Keywords: Regional economics; Spatial economics; Social media; Economic geography; Wireless communication systems; Mobile communication systems; Business information services; Quantitative research; Regional and Spatial Economics; Social Media; Economic Geography; Wireless and Mobile Communication; IT in Business; Data Analysis and Big Data